Early stage design decisions: the way to achieve sustainable buildings at lower costs - Bragança, L. (2014)
The construction industry attempts to produce buildings with as lower environmental impact as possible. However, construction activities still greatly affect environment; therefore, it is necessary to consider a sustainable project approach based on its performance. Sustainability is an important issue to consider in design, not only due to environmental concerns but also due to economic and social matters, promoting architectural quality and economic advantages. This paper aims to identify the phases through which a design project should be developed, emphasising the importance and ability of earlier stages to influence sustainability, performance, and life cycle cost. Then, a selection of sustainability key indicators, able to be used at the design conceptual phase and able to start predicting environmental sustainability performance of buildings is presented. The output of this paper aimed to enable designers to compare and evaluate the consequences of different design solutions, based on preliminary data, and facilitate the collaboration between stakeholders and clients and eventually yield a sustainable and high performance building throughout its life cycle.